Vocational training, basic formation or general formation: what students from a public university in Brazil think - Pereira, Elisabete M. A. (2014)
Abstract: In the context of higher education, student participation in curriculum design is little emphasized. This work results from a research developed with students from all courses at the State University of Campinas – Unicamp - Brazil, with the aim of knowing their perspective regarding which curricular aspects of profesional careers are considered to be seen as essential, and which would be the main curricular emphasis that should be applied in order to better prepare them for the current and the future world of work. The data reveal that students today are more concerned with social issues than they have been in the past and resent not see this emphasis addressed in the curriculum. The research is relevant for giving voice to students’ opinion, once they play an important role in transforming the curriculum intended to a experienced curriculum.